FACTORS THAT INFLUENCE STUDENTS’ LEARNING OF STATIC SUBJECT AT CLASS X TKB SMKN 5 PADANG - 929-948 , Alvino Kurniawan (CIVED, 2016)
ABSTRACTThis research is purposed to reveal factors that influence students’ learning of static subject at class X TKB SMKN 5 Padang. In this research, there is one single variable that is factors that influence students’ learning that being reviewed from internal and external factors of student. This research was descriptive quantitative. Subject in this research was students of class X TKB who was entered static subject on school period of 2014/2015 in SMKN 5 Padang. Sample collection technique was total sampling with sample amounted to 28 students. Data collection instrument was questionnaire that distributed to respondents. Data analysis technique was descriptive analysis with percentage. Research finding shows that factors that influence students’ learning that comes from internal factor gives an influence of 48% toward learning process, while factor that comes from external factor gives an influence of 52%. From both factors that being studied, the rest is not very different so that there is no dominant factor that influence students’ learning.Keywords: internal and external factors, student